Advances in cancer immunotherapy from serendipity to cure - Honjo, T. (Tasuku) 1942-; Gonzalez, Andrew (2021)
Cancer immunotherapy with anti-PD-1 antibodies has fundamentally changed the way we think about cancer treatment. As HONJO Tasuku traces the arc of his research from a serendipitous discovery to the development of a revolutionary therapy, he engages in a wide ranging discussion of the marvels of biological phenomena, the thrill of life science's explorations of the unknown, the nature of life itself, and the future of Japanese healthcare. In the preface to the English edition, Dr. Honjo shares his thoughts about how we should grapple with life in the time of COVID-19 and offers a message to the next generation. Included at the end of the book is the transcript of Dr. Honjo's Nobel Prize banquet speech."--Publisher's description
Includes bibliographical references (pages 149-150) and index.
Keywords: Cancer -- Immunotherapy